Does the intensive grazing and aridity change the relations between the dominant shrub Artemisia kopetdaghensis and plants under its canopies?. Issue 20 (22nd September 2021) - Rahmanian, Soroor; Ejtehadi, Hamid; Farzam, Mohammad; Hejda, Martin; Memariani, Farshid; Pyšek, Petr
Abstract: The interspecific plant interactions along grazing and aridity stress gradients represent a major research issue in plant ecology. However, the combined effects of these two factors on plant–plant interactions have been poorly studied in the northeast of Iran. To fill this knowledge gap, 144 plots were established in 12 study sites with different grazing intensities (high vs. low) and climatic characteristics (arid vs. semiarid) in northeastern Iran. A dominant shrub, Artemisia kopetdaghensis, was selected as the model species. Further, we studied changes in plant life strategies along the combined grazing and aridity stress gradients. In this study, we used relative interaction indices calculated for species richness, Shannon diversity, and species cover to determine plant–plant interactions using linear mixed‐effect models (LMM). The indicator species analysis was used to identify the indicator species for the undercanopy of shrub and for the adjacent open areas. The combined effects of grazing and aridity affected the plant–plant interactions and plant life strategies (CSR) of indicator species. A. kopetdaghensis showed the highest facilitation effect under high stress conditions (high grazing, high aridity), which turned into competition under the low stress conditions (low grazing, low aridity). In the arid region, the canopy of the shrub protected ruderals, annual forbs, and grasses in both high and low grazing intensities. In the semiarid region and high grazing intensity (low aridity/high grazing), the shrubs protected mostly perennial forbs with C‐strategy. Our findings highlight the importance of context‐dependent shrub management to restore the vegetation damaged by the intensive grazing. Abstract : The manuscript is based on a field study, aiming to compare the canopy effects of an unpalatable dominant shrub ( Artemisia kopetdaghensis ) in the conditions of biotic stress, represented by intensive grazing and abiotic stress, represented by severe aridity. Our results bring new evidence to the current debate on the relative importance and characteristics of plant–plant interactions along the gradients of environmental stress. We detected the facilitative effects of the dominant shrub on species diversity in the presence of both grazing and aridity. However, the facilitative effects turned into competition in the conditions of less severe aridity in the semiarid region.